Protein kinase Cβ is involved in cigarette smoke gas phase-induced ferroptosis in J774 macrophages - Tsunehito Higashi; Haruka Handa; Yosuke Mai; Katsumi Maenaka; Takashi Tadokoro (Elsevier, 2023)
Cigarette smoking is a risk factor for respiratory infection caused by immune cell dysfunction. Cigarette smoke is divided into tar and gas phases. Although the gas phase induces cell death in various cell types, the mechanism for gas phase-induced cell death remains to be clarified. In this study, we have examined the effects of cigarette smoke gas phase on J774 macrophages. Cigarette smoke gas phase and cytotoxic factors in the gas phase induced protein kinase C (PKC)-dependent ferroptosis. Pharmacological studies using isoform-specific PKC inhibitors have revealed that PKCβ is involved in cigarette smoke gas phase-induced ferroptosis in J774 macrophages.